Managing forage for grain: Strategies and mechanisms for enhancing forage production to ensure feed grain security - Ruixuan Xu; Zheng Pu; Shuangxin Han; Hongqian Yu; Chuan Guo; Qingsheng Huang; Yingjun Zhang (Journal of Integrative Agriculture, 2025)
The “Greater Food” approach has replaced the older “taking grain production as a top priority” approach. The importance of feed and forage as the material basis for guaranteeing high-quality development of the livestock industry has gradually become prominent. However, owing to the tradition of “both human staple food and animal feed relying on grain production” in China and the decoupling of feed crop planting and livestock farming, the risk of feed grain security has increased, especially as it relates to the supply of high-quality protein feed ingredients from abroad, which is facing a bottleneck. To ensure food security, effective domestic agricultural production should be adopted. Nevertheless, guaranteeing the supply of high-quality protein feed through domestic soybean production is difficult because of limited arable land; furthermore, pressure on the staple food supply is still extreme. In this article, the historical and realistic implications for the security risks of feed grain in China are analyzed. Proposals are made to separate staple food grains for humans from the feed grain supply for animals and to develop high-quality forage to reduce feed grain use. High-quality forage can be supplied via intercropping with grain crops in arable land and reseeding perennial legumes or grasses into natural grasslands. However, “managing forage for grain” needs to be supported via technical paths and policies as the forage industry develops to effectively increase the capacity to ensure feed grain security.